HIV/AIDS and Tuberculosis in Central Asia : Country Profiles. - Godinho, Joana, 1951- (World Bank working paper, 2004)
Annotation HIV/AIDS and Tuberculosis in Central Asia: Country Profiles is part of the World Bank Working Paper series. These papers are published to communicate the results of the Bank's ongoing research and to stimulate public discussion. The countries of Central Asia are still at the earliest stage of an HIV/AIDS epidemic. However, the region is experiencing steep growth of new HIV cases; related epidemics of injected drug use, sexually-transmitted infections (STIs), and tuberculosis; a high percentage of youth in the total population; and low levels of knowledge about the epidemics. HIV/AIDS and tuberculosis could have devastating effects on human capital, economic development, and health system reform. To address this impending crisis, the World Bank has initiated the study of HIV/AIDS, STIs, and tuberculosis in Central Asia. This study presents country profiles that were developed to inform World Bank management and other stakeholders about the main characteristics of the epidemics. The profiles cover epidemiology; strategic and regulatory frameworks; surveillance; preventive, diagnostic, and treatment activities; non-governmental and partner activities; and available resources. The report summarizes the main issues identified by this initial assessment and recommends further study and action.